Pemurnian Bioetanol Hasil Fermentasi Nira Nipah Menggunakan Proses Destilasi-Adsorpsi Menggunakan Adsorben Silica Gel - Shintia Oktaviani; Chairul Chairul; Silvia Reni Yenti (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
The rapid rate of world population growth conduces demand and supply of fuel is not balance. So that, energy reserves has been depleted in large numbers. Especially fossil fuels which is a main energy. The government has compiled program and policy for development of bioethanol and biodiesel to resolve energy crisis in indonesia which targeted in 2025 can be approximately 15-20% fuels need to fulfill transportation sector and the national industry. This research aims to produce bioethanol fuel grade-adsorption using distillation methods, determine the effect of the ratio of silica gel: bioethanol and height of the adsorbent in the column for producing bioethanol fuel grade. The raw material is bioethanol from nipa sap fermentation results with 13% ethanol content. Ethanol content obtained not too high previously, so that should be took a process that can be increase the purity of bioethanol with distillation process-adsorption. This research divided into two stages. First stage is nipa sap bioethanol distiled up to 96% concentration and second stage is distillation-adsorption using silica gel adsorbent. Independent variables on this research is ratio of silica gel : bioethanol and height of adsorbent in the adsorption column. The most influence process to review bioethanol purification is distillation-adsorption silica gel with ratio: ethanol 1:2 and a height of adsorbent in the column is 3.5 cm with purity of 99,6% and had been categorized fuel grade bioethanol.Keywords: Silica gel, bioethanol, bioethanol fuel grade, nypa, distillation adsorption process